2020
DOI: 10.1111/aos.14629
|View full text |Cite
|
Sign up to set email alerts
|

Association between age‐related macular degeneration and periodontal and peri‐implant diseases: a systematic review

Abstract: The aim of the present systematic review was to assess the association between age‐related macular degeneration (AMD) and periodontal and peri‐implant diseases. The focused question was ‘Is there a relationship between AMD and periodontal and peri‐implant diseases?’ Indexed databases were searched up to and including May 2020 to identify pertinent original studies. The Cochrane Collaboration’s tool was used to assess the risk of bias. Five observational cohort studies were included that assessed the associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…Second, because AMD is associated with cardiovascular disease [ 38 , 39 , 40 , 41 , 42 , 43 , 44 ], renal disease [ 38 , 45 , 46 , 47 ], periodontal disease [ 48 , 49 , 50 , 51 , 52 , 53 ] and Alzheimer’s disease [ 54 , 55 , 56 ], prevention of AMD may also reduce the burden of these common diseases. This would remarkably amplify the clinical significance following the prevention of AMD after metformin use.…”
Section: Discussionmentioning
confidence: 99%
“…Second, because AMD is associated with cardiovascular disease [ 38 , 39 , 40 , 41 , 42 , 43 , 44 ], renal disease [ 38 , 45 , 46 , 47 ], periodontal disease [ 48 , 49 , 50 , 51 , 52 , 53 ] and Alzheimer’s disease [ 54 , 55 , 56 ], prevention of AMD may also reduce the burden of these common diseases. This would remarkably amplify the clinical significance following the prevention of AMD after metformin use.…”
Section: Discussionmentioning
confidence: 99%
“…However, all samples received similar freezing and thawing cycles. Excessive complement activation has been associated also with several diseases and pathologies whose association with periodontitis has been suggested, such as Alzheimer's disease, 30 rheumatoid arthritis, 31 AMD, 32 and lung diseases, 33 involving dysregulations of inflammatory pathways. Since the present study has a cross‐sectional design, conclusions of causality cannot be drawn.…”
Section: Discussionmentioning
confidence: 99%
“… 34 Javed et al considered that periodontal diseases which was mainly caused by the periodontal infection may be a plausible risk factor for AMD and may have a potential role in the earlier stages of this eye disease. 35 Robman et al found that AMD patients with high antibody titers of C. pneumoniae were also found to have a 2- to 3-fold increased risk of disease progression. 36 In our study, AMD subjects with acute infectious diseases were excluded; however, chronic subclinical inflammation in AMD subjects was usually difficult to detect through medical screenings.…”
Section: Discussionmentioning
confidence: 99%